Effect of the substitution of return bagasse (Pachaquil), fermented in solid state and ensiled, on productive performance of cows in the tropics - ?lvarez, L. Y.; Mendoza, G. D.; Aranda, E. M.; Mora, O.; Fern?ndez, P. A.; Garc?a-Bojalil, C. M. (Cuban Journal of Agricultural Science, 2011)
In order to know the effect of the supplement level substitution by return bagasse, fermented in solid state and ensiled, on the performance of growing cows in the tropics, eighteen Bos taurus x Bos indicus cows were used (230 ? 40 kg liveweight). They were allocated in individual pens, in completely randomized design with three supplement combinations: silage 100:0, 50:50, and 0:100 %. During the assay (90 d), daily weight gain (DWG), dry matter intake (DM), and feed conversion were recorded. DWG had quadratic effect (P < 0.01) and showed the best response in the 50:50 combination (0.58, 0.74 and 0.46 kg/d), whereas the conversion was affected (quadratic, P < 0.01) by increasing the rate of silage (12.18, 10.33 and 16.04). No differences were found in the DM intake for the 100:0, 50:50, and 0:100 % combinations (7.07, 7.65 and 7.38 kg/d), respectively. It was concluded that, with the substitution of 50 % of the supplement by RBFSSE, there is better behavior in growing cows in the tropics, using sugarcane diets with 1 % urea. Key words: sugarcane, return bagasse, solid fermentation, cow behavior.